As “Marcas” em Territórios Formados por Grupos Étnicos Alemães a Partir dos Estereótipos Linguagem, Trabalho e Religiosidade: O Caso da Comunidade Rural de Linha Acre – Cândido Godói (RS) - Rejane Inês Kieling (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2020)
The spread of an industrial mentality in rural areas by means of large-scale food production has been driving change in small rural communities that are compelled by necessity to look for alternatives aimed at their continuity not only in physical terms, but also with regard to their social and cultural specifities. This study is focused on identification of aspects related to stereotypes that “mark” territories formed by social groups of German Brazilians as they are considered to be relevant so that said players may find new meanings in the environment they live. This return to the past is only possible by means of recollections and memory that is present in the everyday life and reveals itself in traditions, customs, and habits as something imperceptible but powerful enough to change the future. The technique used for data collection was in-depth interviews in ethnographic research carried out in the Linha Acre rural community, Cândido Godói (RS) in 2016 and 2017. At the data analysis stage, rootedness with regard to stereotyped constructions in such elements as language, work, and religiosity chosen for the research was positively verified.